A strategy to link the changes in the quality traits of Japanese sea bass (Lateolabrax japonicus) muscle and proteins in its exudate during cold storage using mass spectrometry. Issue 6 (16th February 2023) - Li, Xiaoxia; Bi, Hongyan
Abstract : The protein in muscle exudate was linked to the changes in the quality traits of fish muscle during storage via MS analysis and pyramid diagrams, opening up new possibilities for understanding the mechanism of muscle changes at the molecular level. Abstract : In this study, Japanese sea bass ( Lateolabrax japonicus ) was used as a model to link the changes in the quality traits of fish muscle during storage to the change of protein in muscle exudate. Matrix-assisted laser desorption time-of-flight mass spectrometry (MALDI-TOF MS) combined with variables importance in projection (VIP) analysis, and high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS), were applied to identify the proteins by analyzing the enzymatic hydrolysates of exudates of fish muscle. The link in the identified proteins to the change in the quality traits of fish muscle during storage was explored using pyramid diagrams. Nine proteins were identified from the exudate of Japanese sea bass muscle during 12 days of storage at 4 °C. Of these, four proteins, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), heat shock protein 90 (HSP90), and peroxiredoxin 1 (PRX1), and beta-actin were found to be responsible for the changes in the quality traits of fish muscle. It is promising to correlate the changes in the quality traits of fish muscle and proteins in muscle exudate via MS-based protein identification and the construction of a relationship diagram to understand the mechanism of muscle change at the molecular level.